Enhanced proton transport properties of sulfonated polyarylene ether nitrile (SPEN) with moniliform nanostructure UiO-66-NH2/CNT. (November 2021) - Zheng, Penglun; Wang, Rui; Li, Zekun; Li, Youren; Wang, Donghui; Li, Zhifa; Peng, Xiaoliang; Liu, Chuanbang; Jiang, Lan; Liu, Quanyi
Metal-organic frameworks (MOFs) have been widely investigated for their porosity and functional diversity. Inspired by the flexible designability of MOFs, UiO-66-NH2 /CNT with moniliform nanostructure was designed and synthesized successfully. SPEN@UiO-66-NH2 /CNT composite proton exchange membranes were prepared by loaded UiO-66-NH2 /CNT into sulfonated polyarylene ether nitrile (SPEN). Due to the addition of UiO-66-NH2 /CNT, all the properties of composite proton exchange membranes were improved. The composite membranes exhibit excellent thermal stability and dimensional stability. The tensile strength of the composite membranes was improved about twofold compared to that of recast SPEN membrane, which was contributed by the interlaced property and rigid structure of UiO-66-NH2 /CNT. Especially, the proton conductivity of the composite membranes was greatly facilitated by the additional proton acceptors and donors provided by the abundant amino groups and carboxyl groups in UiO-66-NH2 /CNT. Furthermore, the methanol permeability of SPEN@UiO-66-NH2 /CNT reduced consistently (from 6.13 to 0.96 × 10 −7 cm 2 s −1 ), which was much lower than that of Nafion membrane (21.36 × 10 −7 cm 2 s −1 ). All the results suggest that the design of multifunctional nanofillers based on the skeleton structure of MOFs could provide a new strategy to enhance the performance of PEMs.